Bonhoeffer and continental thought: cruciform philosophy - Gregor, Brian; Zimmermann, Jens (Indiana series in the philosophy of religion, 2009)
Dietrich Bonhoeffer and cruciform philosophy / Brian Gregor and Jens Zimmermann -- Bonhoeffer on the uses and limits of philosophy / Christiane Tietz -- Bonhoeffer, this-worldliness, and the limits of phenomenology / Paul D. Janz -- Aristocratic christendom : on Bonhoeffer and Nietzsche / Frits de Lange -- "Who stands fast?" : do philosophers make good résistants? / Jean Greisch -- Dietrich Bonhoeffer and Martin Heidegger : two different visions of humanity / Jens Zimmermann -- Philosophical influences on Bonhoeffer's "religionless Christianity" / Ralf K. Wüstenberg -- The non-religious interpretation of Christianity in Bonhoeffer / Paul Ricoeur -- Bonhoeffer's "religious clothes" : the naked man, the secret, and what we hear / Kevin hart -- Bonhoeffer's "Christian social philosophy" : conscience, alterity, and the moment of ethical responsibility / Brian Gregor -- "At the recurrent end of the unending" : Bonhoeffer's eschatology of the penultimate / John Panteleimon Manoussakis